Applying computers in English language teaching and learning - Негара, Родіон Віталійович; Негара, Р. В.; Негара, Родион Витальевич; Nehara, Rodion V.; Магновський, Ігор Йосифович; Магновський, І. Й.; Магновский, Игорь Иосифович; Mahnovskyi, Ihor Y.; Стець, Олег Миколайович; Стець, О. М.; Стец, Олег Николаевич; Stets, Oleh M. (FCLAR, 2021)
In the prevailing era, the positive effect of using the media, especially computers, is not hidden from anyone and based on this, the use of multimedia in teaching English can play a significant role because of the various possibilities that the use of multimedia. In this regard, it can be effective in increasing the amount of learning as well as recall. For this reason, in this study, an attempt has been made to investigate the impact of computer use on learning and teaching English lessons among students of Ukraine University and a more apparent reason for claiming the positive effect of computer use in education, especially language teaching. A descriptive-analytical method is used to meet the aim of the study. In conclusion, the article reveals the beneficial effect of applying computers in English language teaching and learning along with some advantageous recommendations.

У сучасну епоху позитивний ефект від використання засобів медіа, особливо комп’ютерів, ні від кого не приховується, і виходячи з цього, використання мультимедіа у навчанні англійської мови може відігравати значну роль через різноманітні можливості використання мультимедіа. У цьому відношенні він може бути ефективним для збільшення обсягу навчання, а також запам’ятовування. З цієї причини в даному дослідженні зроблено спробу дослідити вплив використання комп’ютера у навчанні та викладанні уроків англійської мови студентами Університету України та більш очевидну причину стверджувати про позитивний ефект використання комп’ютера в освіті, особливо у викладанні мови. Для досягнення мети дослідження використовується описово-аналітичний метод. На завершення стаття розкриває сприятливий ефект від застосування комп’ютерів у викладанні та навчанні англійської мови разом із деякими корисними рекомендаціями.
Mahnovskyi I. Y. Applying computers in English language teaching and learning / I. Y. Mahnovskyi, O. M. Stets, R. V. Nehara // Revista EntreLinguas. - V. 7. - no. esp. 7. - FCLAR, 2021. - 14 р.
Keywords: computers; multimedia; teaching English; students; комп’ютери; мультимедіа; викладання англійської мови; студенти; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education